A fully radiopaque hybrid stent retriever versus a precursor device: Outcome, efficacy, and safety in large vessel stroke. Issue 5 (12th April 2022) - Weiss, Daniel; Kabbasch, Christoph; Lichtenstein, Thorsten; Turowski, Bernd; Kaschner, Marius
Abstract: Background and Purpose: The aim of this multicenter study was to compare the clinical outcome, safety, and efficacy of the full‐length radiopaque Aperio Hybrid stent retriever (APH) with the precursor Aperio thrombectomy device (AP). Methods: Multicentric retrospective analysis of patients with stroke, treated with the APH and AP due to an acute ischemic stroke by large vessel occlusions in the anterior or posterior circulation, was performed. We focused on the comparison of favorable clinical outcome (modified Rankin Scale, 0‐2) after 3 months, favorable reperfusion rates (thrombolysis in cerebral infarction scale ≥ 2b), and the complication rate. Results: A total of 51 patients (female: n = 33, 64.7%, mean age 73 ± 16 years) with a median baseline National Institutes of Health Stroke Scale: 15 were treated with the APH or AP. Favorable outcome in patients treated with APH was excellent (44.0%) and comparable to the AP (36.8%). The rate of final favorable reperfusion for both devices was outstanding (APH 31/31 and AP 20/20). The overall complication rate for the APH was slightly higher compared to the AP (32.3%/15.0%). Symptomatic intracranial hemorrhage was recorded in 0 of 51 cases. The all‐cause mortality rate at 90 days was 20.0% for the APH and comparable for the AP (21.1%). Conclusions: Comparable clinical outcome, efficacy, and safety of the AP and the recently introduced APH were demonstrated. Both devices appeared feasible, efficient, and safe with regard to endovascular treatment in large vessel occlusion.